Comparing Open vs Minimally Invasive Techniques for the Correction of Hallux Valgus: Clinical and Patient Reported Outcomes. Issue 1 (January 2022) - Chrea, Bopha; Day, Jonathan; Dean, Daniel M.; Cortina, Rose E.; Reilly, Megan; Caolo, Kristin C.; Cerrato, Rebecca A.; Johnson, A.
Category: Bunion Introduction/Purpose: Multiple operative techniques have been developed for hallux valgus with varying success. While correction has been traditionally achieved through open surgical approaches, there has been a growing interest in minimally invasive surgical (MIS) techniques. The purpose of this study was to compare clinical and patient-reported outcomes for patients undergoing hallux valgus correction with Lapidus, Scarf and MIS. Our hypothesis was that while a superior clinical correction would be achieved with open techniques there would be similar patient-reported outcomes among open and MIS techniques. Methods: A total of 257 patients who underwent Lapidus (n=82), Scarf (n=82) or MIS (n=93) hallux valgus correction between January 2017- January 2020 at one of two academic institutions by 1 of 9 foot and ankle-fellowship trained orthopedic surgeons were included in this study. Only 3 of 9 performed MIS correction. The average age at the time of surgery 55.4 (range 14-79). Patients were required to have a minimum baseline and 1-year postoperative Patient-Reported Outcomes Measurement Information Scores (PROMIS) and minimum 3-month clinical follow-up. Retrospective chart review was performed to assess the incidence of postoperative complications and reoperations, with an average clinical follow-up of 8 months. Results: All groups had statistically significant differences between pre- and post-operative measurements of HVA, IMA, DMAA, and tibial sesamoid position (<0.05). In addition, the Lapidus group demonstrated change in all parameters measured including Meary's angle, sagittal IMA and Seiberg index. All groups had statistically significant improvement in the PROMIS physical function, pain interference, and global health physical at 1 year (p<0.05). The Lapidus group had significant improvement in all 6 PROMIS domains measured. There were no significant differences in PROMIS score changes from pre to post-op for any PROMIS domain when comparing MIS vs Scarf vs Lapidus. Complications: Minor Complications were classified as infection, symptomatic hardware, delayed union, nerve irritation, transfer metatarsalgia (Lapidus n=14 (17.1%), Scarf n=2 (2.4%), MIS n=15 (16.1%)). Major complications were classified as nonunion, recurrence, hallux varus, recurrence (HVA >20) (Lapidus n=7 (8.5%), Scarf n=9 (11.0%), MIS n=9 (9.7%)). Conclusion: In the last decade, there has been a growing interest in the use of minimally invasive surgical MIS techniques for the treatment of hallux valgus. When compared with traditional open techniques using Lapidus and Scarf osteotomies MIS presents a safe and effective approach to treating hallux valgus.